Research perspective: the “spirit” of capitalism and its supporting classes - Pohlmann, Markus (Global economic elites and the new spirit of capitalism, 2024)
The “spirit” of capitalism is a cipher in the scientific discussion about the development of capitalism. The discourse of the “spirit” obviously invites speculation and the associations are manifold, which generates such an expression. Weber’s work, from which we draw the term and the concept, is also conceived in a rather cautiously groping manner in this aspect (see also a recent criticism of this, Steinert 20,100).
Gesehen am 27.06.2024